The Recent Research Development on Micro Small and Medium Enterprises in Indonesia - Latifah, Lyna; Setiawan, Doddy; Aryani, Y. Anni (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
The purpose of this study is to describe the reseach development on Micro Small and Medium Enterprises (MSMEs) in Indonesia. It analyzes the articles which published in accredited national journals from 2009-2017. The samples of this research are 96 articles from 27 journals. The result of the study shows that researches on MSMEs from 2013 to 2017 have increased. The journal which actively publishes the MSMEs articles is Jurnal Aplikasi Manajemen which published 20 articles (20%). The most frequently topics discussed on MSMEs in the last decade are on strategy of MSMEs for 28 articles (29%). Furthermore; 77 articles (80%) used the quantitative method and only 25 articles (26%) were successfully cited by other articles. Recomendation for future reseach to explore taxation research with experimental methods.